Dual-Element PIFA Design with Dual Shorting Pins for Multiband Communication Devices - Muhammad Sajjad Ahmad; Che Young Kim (International Journal of Antennas and Propagation)
A low profile multiband resonant, dual-element array antenna is proposed for use in handheld communication devices. The proposed antenna comprises two dual shorting pin planar inverted-F antennas and a folded ground plane which operates as a perfect electric conductor case. The feeding scheme adopted for the proposed design produces a fixed phase difference between two antenna elements of the design to achieve an ultrawide bandwidth and a flexible radiation pattern. The proposed antenna design is simulated with commercially available software, which is based on the finite element method. The resonant frequency bands covered are GSM850/900, DCS1800, PCS1900, UMTS2100, and LTE2300/2600 MHz. Details of the design considerations for the proposed antenna are described and the simulated and measured results are presented and discussed, which are in agreement.